Hemodynamics of Right Heart in Healthy Children according to Doppler Echocardiography - V.A. Kondratiev; A.V. Reznik; E.V. Kunak (Zaslavsky O.Yu., 2015)
There was studied intracardiac hemodynamics in 96 healthy children aged from 3 to 15 years old. There were identified age-related standards for dopplerechocardiography parameters of right heart, which can be used for the diagnosis of pathological abnormalities of the cardiac functionality in children with cardiac and somatic pathology in the practice of pediatrics and pediatric cardiology. The use of standardized methodological approaches to the assessment of systolic and diastolic function of the right ventricle will allow compare the results of studies obtained in different clinics, and use these data in scientific research.